Prevalence of Preoperative Iron Deficiency Anemia: A Case Series Among Patients Undergoing Radical Cystectomy. Issue 5 (May 2021) - Patel, Sephalie Y.; Kubal, Timothy E.; Li, Roger; Manley, Brandon J.; Gilbert, Scott M.; Sexton, Wade J.; Spiess, Philippe E.; Boulware, David; Poch, Michael A.
Abstract : Anemia occurs in a significant group of patients with bladder cancer before radical cystectomy. Iron deficiency is a readily identifiable cause of anemia, which can be treated before surgery. The proportion of patients with bladder cancer with iron deficiency anemia is unknown. Laboratory and clinical outcomes were collected on 47 consecutive patients presenting for radical cystectomy. Iron studies found 30% of patients had iron deficiency anemia. These findings present an opportunity to treat anemia before surgery, to reduce blood transfusions during radical cystectomy.